Time to learn from the Saudis - Abd Razak, Dzulkifli (2010)
This time it had successfully attracted more than over 300 universities from more than 30 countries to participate in its inaugural International Exhibition for Higher Education in Riyadh last week. Some 30 Saudi Arabian universities also took part, including the recently founded Princess Nora Bint Abdulrahman University situated in Riyadh, the first women’s college in Saudi Arabia the country. It was only a few years ago that the number of universities in the Kingdom was less than 10.